The Research Library and Scholarly Information; a Future for Librarians? - Klugkist, Alex C. (LIBER Quarterly: The Journal of the Association of European Research Libraries, 2002)
The development of information technology reminds me in many ways of the discovery of the printing press. They both have given rise to revolutionary new ways of disseminating information faster and on a broader scale. In the 15th century, no one had any awareness of the enormous impact that printing was to have. The first printed works were remarkably similar in appearance to the manuscripts that preceded them, and have consequently been termed „cradle books” (incunabula). Printing technology’s effect on the community at large was only gradual, and in the initial stages affected the dissemination of learning and culture only to a minor degree. This had little to do with the new ways of producing information or the form the information was in; it was mainly because only few people had access to education and culture. Researchers were few in number. Long after the rise of printing, academics were still exchanging ideas and research results by journeying to do so in person or by corresponding with each other. It was the way they had always transmitted their knowledge, and they remained true to the tradition.